Cognitive-inspired speaker affective state profiling - Norhaslinda Kamaruddin (2013)
Human behavior is influenced by emotion and human expressed affective state through numerous channels using non-verbal communication; namely: facial expression, gestures, eye-gazing, body postures, as well as verbal communication. In verbal communication itself, there are lots of underlying information transmitted using acoustical features and the semantic meaning of the word/sentence used. Despite the evident complexity of such interaction, listener still can correctly perceive the propagated emotion conveyed by the interlocutor. This is due to the human cognitive functional ability to dissect and infer the information with high accuracy and then react accordingly with appropriate behavioral responses and feedbacks. Hence, this research work introduces novel technique in discriminating emotion to facilitate the understanding of speaker affective state, based on the hypothesis that emotion is propagated through speech and it can be quantified.